P Persepsi Masyarakat Terhadap Pengobatan Menggunakan Tanaman Herbal Di Wilayah Sungai Lulut Banjarmasin Berdasarkan Theory Of Planned Behavior - Arga, Ine Andriani (LPPM Universitas Sari Mulia, 2025)
Background: Perceptions regarding medication use vary, including the use of herbal medicines, the experience of information obtained by the community can influence perceptions about treatment, so it is necessary to see how the community perceives it in making treatment decisions. Objective: Knowing the relationship between public perception through the Theory of Planned Behavior approach and treatment behavior using herbal plants. Methods: Analytical observational research with cross sectional. Sampling was carried out using purposive sampling technique. The research sample consisted of 100 respondents. Data was obtained using a questionnaire distributed to the public and analyzed using the Spearman' rho statistical test. Results: The results showed that 91% of respondents had a strong attitude towards carrying out treatment using herbal plants, 87% of respondents had a good attitude towards carrying out treatment using herbal plants, 88% of respondents had a high subjective norm of confidence in carrying out treatment using herbal plants, 83% Respondents have high behavioral control to support or inhibit people's behavior towards treatment using herbal plants. Attitude variables do not have a significant relationship with treatment behavior using herbal plants p value= (0.910), subjective norms have a significant relationship with treatment behavior using herbal plants p value= (0.013) and behavioral control does not have a significant relationship with treatment behavior using herbal plants p value= (0.072). Conclusion: The test results in this study show that there is no relationship between attitudes and behavioral control and people's behavior in carrying out treatment using herbal plants, while subjective norms show that there is a relationship with people's behavior in carrying out treatment using herbal plants using the Theory of Planned Behavior approach